(untitled) (Research, Society and Development, 2023)
Pyometra is the most common infectious disease of the reproductive system in bitches. It is considered a disease of great complexity and if not diagnosed and treated in time, it can lead to the death of the bitch. The purpose of this article is to report the efficacy of conservative treatment in a bitch diagnosed with pyometra and her subsequent return to reproductive function. This is a 12-month-old female French Bulldog that presented with apathy, dehydration, hyperthermia, hyporexia, abdominalgia, and mucopurulent vulvar discharge. The presumptive diagnosis of pyometra was based on the extravasation of purulent contents through the vulva, which was confirmed by ultrasonography. The treatment initiated was based on the administration of aglepristone (Alizin® Virbac) and combinations with antibiotic therapy, antiphlogistic drugs, analgesic, and gastric protector, which proved to be effective for the clinical cure of the animal. After three years, the animal was subjected to artificial insemination and pregnancy was confirmed, with uneventful gestation and birth of two puppies. The treatment in question was considered effective because it promoted the clinical cure of the animal, the complete involution of the uterus and the return of reproductive viability.